A Common 4G Allele in the Promoter of the Plasminogen Activator Inhibitor-1 (PAI-1) Gene as a Risk Factor for Pulmonary Embolism and Arterial Thrombosis in Hereditary Protein S Deficiency - Zöller, Bengt; Frutos, Pablo García de; Dahlbäck, Björn (Thrombosis and Haemostasis, 1998)
Reduced fibrinolytic capacity due to increased plasminogen activator inhibitor-1 (PAI-1) activity in plasma is a common finding in patients with coronary heart disease or venous thromboembolism, although its clinical significance is debated. Recently, a dimorphism in the PAI-1 promoter (4G-5G) has been reported and homozygosity for the 4G allele is associated with increased transcription and higher PAI-1 levels. Homozygous 4G genotype has been suggested to be a risk factor for myocardial infarction. In the present study, the 4G-5G dimorphism was determined in 349 individuals from 21 thrombophilic families with hereditary protein S deficiency and in 140 unrelated healthy controls. Among the 143 protein S deficient individuals, there was no relationship between deep or superficial venous thrombosis and the PAI-1 dimorphism. However, 26% (12/46) of individuals having protein S deficiency combined with homozygosity for the 4G allele had suffered pulmonary embolism as compared to 7% (7/97) of protein S deficient individuals carrying at least one 5G allele (p = 0.0019). In protein S deficient individuals, arterial thrombosis was found to be associated with smoking and 4G homozygosity. No association was found between the PAI-1 dimorphism and arterial or venous thromboembolism in family members without protein S deficiency. In conclusion, the PAI-1 genotype affects the phenotypic expression of thrombophilia in protein S deficient individuals.